2010
DOI: 10.1021/pr100621g
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Human Adipocyte Secreted Proteins by Using SGBS Cells

Abstract: Adipose tissue is an endocrine organ secreting different types of proteins, known as adipokines. These adipokines play important roles in homeostasis and metabolism. Adipocyte differentiation leads to a change in adipokine secretion profile which is probably involved in disruption of homeostasis. Many adipokines have been identified but species differences and limitations of human adipose tissue material urged the need for better model systems. Here we used a human cell strain derived from a Simpson Golabi Beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 62 publications
3
46
0
Order By: Relevance
“…In addition, other proteins (supplemental Table 3) were found to be over-represented across the various amyloidoses, including clusterin, 17 apolipoprotein E, 18,19 apolipoprotein A-IV, 20 vitronectin, 18 basement membrane-specific heparan sulfate proteoglycan core protein, 21 sushi-repeat-containing protein, and serum amyloid P. 22 Most of these had previously been described as associated with amyloid fibrils and involved in the mechanisms of amyloid formation; this confirms that MudPIT can fully characterize the deposits in whole adipose tissue and constitutes an internal validation parameter. In addition, sushi-repeat-containing protein may play a role in amyloid disease; indeed, it is secreted by adipocytes 23 and may intervene in adipogenic differentiation, 24 regulation of body weight, and metabolism. 24,25 Moreover, evidence of its involvement in tumor suppression, possibly through apoptosis induction, 26 emphasizes its potential interest in amyloid cell toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, other proteins (supplemental Table 3) were found to be over-represented across the various amyloidoses, including clusterin, 17 apolipoprotein E, 18,19 apolipoprotein A-IV, 20 vitronectin, 18 basement membrane-specific heparan sulfate proteoglycan core protein, 21 sushi-repeat-containing protein, and serum amyloid P. 22 Most of these had previously been described as associated with amyloid fibrils and involved in the mechanisms of amyloid formation; this confirms that MudPIT can fully characterize the deposits in whole adipose tissue and constitutes an internal validation parameter. In addition, sushi-repeat-containing protein may play a role in amyloid disease; indeed, it is secreted by adipocytes 23 and may intervene in adipogenic differentiation, 24 regulation of body weight, and metabolism. 24,25 Moreover, evidence of its involvement in tumor suppression, possibly through apoptosis induction, 26 emphasizes its potential interest in amyloid cell toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 98 proteins identified by mass spectrometry, adiponectin, cystatin C, resistin, adipsin, metalloproteinase inhibitor 1, chemerin, Vim, Sparc, and Vitamin D-binding protein are known adipokines (13,(26)(27)(28)(29). Taking into account which proteins have been reported to be secreted by adipocytes and adipose tissue, we identified Cpq, Got2, and Ecm1 as potential novel adipokines.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the relevance of adipose tissue in the progression of these common diseases, multiple unbiased, proteomic approaches have characterized the secretome from both rodent and human adipocytes and adipose tissue (10)(11)(12)(13)(14)(15)(16)(17). These studies have emphasized the complex nature of the adipokinome and have identified hundreds of adipokines.…”
Section: Sds-page/liquid Chromatography-electrospray Ionization Tandementioning
confidence: 99%